The Effect of Social Media Marketing and Brand Image on Purchase Decisions in Somethinc Products - Ismi Avia Febriyanti; Imanuddin Hasbi (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
This study aims to examine and analyze the influence of social media marketing and brand image on purchasing decisions on somethink products. This study used data collection techniques with questionnaires distributed via the Google Form platform with a sample of 108 people as research respondents. The analytical method used is multiple linear regression analysis. The software used in this research is SPSS version 25. The results showed that social media marketing and brand image had a positive and significant effect on somethink products. The results of data processing show that social media marketing and brand image (X) have an influence on the purchasing decision variable (Y) of 58.5% while the remaining 41.5% is influenced by other variables not examined in this study.